Analysis of a free boundary problem for vascularized tumor growth with a necrotic core and time delays. (August 2023) - Xu, Shihe; Xuan, Zuxing
Abstract: In this paper a free boundary problem for vascularized tumor growth with a necrotic core and time delays is studied. In the problem, there are two free boundaries, one is the outer boundary of the tumor, the other is the necrotic core boundary inside the tumor. The time delay exists in the process of tumor growth and represents the time required for tumor cell division. Sufficient conditions for the existence, uniqueness and stability of the stationary solution to the model are given. The results show that the time delay does not affect the final growth behavior of tumor.